An Augmented Cobb-Douglas Production Function Modeling of the Impact of Climate Change on Maize Yields in Ethiopia - Abera Gayesa Tirfi; Abayomi Samuel Oyekale (Agro Ekonomi, 2023)
Climate change remains a major problem confronting agricultural productivity in Ethiopia. Maize and some other cereal crops are susceptible to climatic parameters. This study analyzed the impacts of some climatic variables on the yields of maize crops in Ethiopia using the 1981-2018 dataset. Maize production in Ethiopia is adversely affected by climate change. The augmented Cobb-Douglas Production function was used for data analyses. The results showed that the parameters of long-season rainfall, short-season rainfall, and mean maximum temperature show a negative sign and are statistically significant (p<0.05). In contrast, the minimum temperature shows a positive sign. In addition, the parameters of the quantity of fertilizer and improved seed used in maize production have a positive and significant impact on the yields of maize (p<0.10). However, the land area's elasticity coefficient shows a negative and statistically significant sign. It was concluded that changes in climatic parameters, such as an increase in short-season and long-season rainfall and an increase in maximum temperature, would reduce maize productivity. Therefore, utilizing effective climate change adaptation measures promises to enhance maize productivity in Ethiopia.